Investigation of cast and annealed Ti25Nb10Zr alloy as material for orthopedic devices - Bolmaro, Raul Eduardo (2019)
In the present work, we report the preparation of a novel titanium-based alloy, namely Ti25Nb10Zr, by cold crucible levitation melting technique. The cast alloy consists of a complex microstructure with large Beta phase grains (54%, 50-150 μm) with a regularly connected net of Alpha′ (orthorhombic, 46%) phase running along boundaries and across the grains and keeping a regular misorientation with respect to the Beta phase. An intermeshed 51% Alpha and 49% Beta phases with lamellar microstructure were found by annealing. The electrochemical tests showed that both alloys were affected by the corrosion process. A good corrosion resistance in SBF at 37 °C was found for the cast form. The cast alloy is more resistant when immersed into solutions with pH2 and pH7, while the annealed one is resistant in pH5 solution. Surface potential of both alloys is negative, with the annealing process leading to a slight decrease of that property. Collectively, the biological results indicate a more favorable viability on cast form as compared to annealed one, suggesting that the cast alloy is promising for biomedical applications.